PENGARUH GENDER DAN KECERDASAN EMOSIONAL TERHADAP MAHARAH KITABAH SISWA - M.Fajri; Ahmad Tarmizi; Nazarmanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of gender and emotional intelligence on students’ maharah kitabah (writing skill). The background of this study is based on the fact that students’ writing ability in Arabic is still relatively low and is influenced by various internal factors, including gender differences and emotional intelligence. This research uses a quantitative approach with a causal-comparative design. The subjects of this study consisted of 31 students, including 14 male and 17 female students.Data collection techniques included questionnaires to measure emotional intelligence and tests to assess students’ maharah kitabah. The data were analyzed using Independent Sample T-Test to examine differences based on gender and simple linear regression to determine the effect of emotional intelligence. The results of the study show that there is a significant difference in students’ maharah kitabah based on gender, with a significance value less than 0.05. Meanwhile, the result of the regression analysis shows that emotional intelligence does not have a significant effect on maharah kitabah, with a significance value of 0.102 (p > 0.05). In conclusion, gender plays a role in differentiating students’ writing abilities, while emotional intelligence does not show a significant influence in this study. These findings indicate that individual characteristics, particularly gender, have a stronger contribution to students’ maharah kitabah compared to emotional intelligence.